Behold! Alpha and Beta are on their way!

Level pending

Let α n \alpha_{n} and β n \beta_{n} be the roots of

x 2 + ( 2 n + 1 ) x + n 2 x^2+(2n+1)x+n^2

The sum of

1 ( α 3 + 1 ) ( β 3 + 1 ) + 1 ( α 4 + 1 ) ( β 4 + 1 ) + + 1 ( α 20 + 1 ) ( β 20 + 1 ) \frac{1}{(\alpha_{3}+1)(\beta_{3}+1)}+\frac{1}{(\alpha_{4}+1)(\beta_{4}+1)}+\ldots+\frac{1}{(\alpha_{20}+1)(\beta_{20}+1)}

can be expressed as a b \frac{a}{b} , where a a and b b are coprime positive integers.

What is the value of b a b-a ?


The answer is 229.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Notice that α n β n = n 2 \alpha_{n} \beta_{n} = n^{2} and α n + β n = ( 2 n + 1 ) \alpha_{n} + \beta_{n} = -(2n+1) from Vieta's formula.

Consider the expression ( α n + 1 ) ( β n + 1 ) (\alpha_{n}+1)(\beta_{n}+1) .

= α n β n + α n + β n + 1 = \alpha_{n} \beta_{n} + \alpha_{n} + \beta_{n} + 1

= n 2 2 n = n^{2} - 2n

= n ( n 2 ) = n(n-2) ...

Therefore, 1 ( α n + 1 ) ( β n + 1 ) \frac{1}{(\alpha_{n}+1)(\beta_{n}+1)}

= 1 n ( n 2 ) = \frac{1}{n(n-2)}

= 1 2 ( 1 n 1 n 2 ) = \frac{1}{2} (\frac{1}{n} - \frac{1}{n-2})

The summation from n = 3 n = 3 to 20 20 is...

= 1 2 ( 1 + 1 2 1 19 1 20 ) = \frac{1}{2} (1 + \frac{1}{2} - \frac{1}{19} - \frac{1}{20})

= 531 760 = \frac{531}{760}

The answer is 760 531 = 229 760 - 531 = \boxed{229} ~~~

Confession: I kept adding 2 numbers together and not realized until I looked at the question... T__T

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...